China's long march towards the twin peaks model of financial regulation. Issue 1 (3rd April 2021) - Kang, Yuan; Schmulow, Andrew; Godwin, Andrew
ABSTRACT: This article traces the evolution of China's financial regulatory system, and its trend towards what could be referred to as a 'quasi-Twin Peaks' model. It then outlines the ongoing challenges with the current sector-based framework, including regulatory competition, regulatory arbitrage and inconsistent regulatory mandates. It then proposes a pathway by which China could adopt a true Twin Peaks model. Finally, the article outlines recent developments in consumer protection, and draws parallel with developments in two Twin Peaks jurisdictions: the UK and South Africa. The article concludes by arguing that the adoption of an overarching framework for consumer protection in banking products and payment services underscores the need for a unified framework that applies to all products and services in the financial sector, including those administered by the CSRC in the securities sector. It also highlights the benefits of separating market conduct and consumer protection regulation, from macro-prudential and micro-prudential regulation, and provides additional support for the argument that the ultimate destination to which China should march, is the Twin Peaks model of financial regulation. This would be in line with the emerging direction of China's regulatory agency reform, and would better accommodate ongoing financial innovation and cross-sector cooperation and integration.